Foot orthoses in the treatment of symptomatic midfoot osteoarthritis using clinical and biomechanical outcomes: a randomised feasibility study. Issue 4 (April 2016) - Halstead, Jill; Chapman, Graham; Gray, Janine; Grainger, Andrew; Brown, Sarah; Wilkins, Richard; Roddy, Edward; Helliwell, Philip; Keenan, Anne-Maree; Redmond, Anthony
Abstract This randomised feasibility study aimed to examine the clinical and biomechanical effects of functional foot orthoses (FFOs) in the treatment of midfoot osteoarthritis (OA) and the feasibility of conducting a full randomised controlled trial. Participants with painful, radiographically confirmed midfoot OA were recruited and randomised to receive either FFOs or a sham control orthosis. Feasibility measures included recruitment and attrition rates, practicality of blinding and adherence rates. Clinical outcome measures were: change from baseline to 12 weeks for severity of pain (numerical rating scale), foot function (Manchester Foot Pain and Disability Index) and patient global impression of change scale. To investigate the biomechanical effect of foot orthoses, in-shoe foot kinematics and plantar pressures were evaluated at 12 weeks. Of the 119 participants screened, 37 were randomised and 33 completed the study (FFO = 18, sham = 15). Compliance with foot orthoses and blinding of the intervention was achieved in three quarters of the group. Both groups reported improvements in pain, function and global impression of change; the FFO group reporting greater improvements compared to the sham group. The biomechanical outcomes indicated the FFO group inverted the hindfoot and increased midfoot maximum plantar force compared to the sham group. The present findings suggest FFOs worn over 12 weeks may provide detectable clinical and biomechanical benefits compared to sham orthoses. This feasibility study provides useful clinical, biomechanical and statistical information for the design and implementation of a definitive randomised controlled trial to evaluate the effectiveness of FFOs in treating painful midfoot OA.